Sleep Habits, Quality of Life and Psychosocial Aspects in the Older Age: Before and During COVID-19 - Almondes, Katie Moraes de; Castro, Eleni de Araujo Sales; Paiva, Teresa (Frontiers in Neuroscience, 2022)
Aim This study aimed to describe sleep habits, quality of life and psychosocial aspects in older people and analyze associated differences considering the time before COVID-19 pandemic and during its first wave in Portugal. Methods Online survey used for data collection received answers from 914 elderly (age range 65 – 90y), from April to August 2020. Results Symptoms of self-perception of depression, anxiety, irritability and economic problems were not prominent in the elderly, except for worries concerning uncertainty about the future. There was no difference in sleep duration before and during the pandemic, although there was a worsening of some aspects related to sleep, such as sleep quality, sleep efficiency, awakening quality, sleep latency and nocturnal awakenings. Gender comparisons showed a higher vulnerability in women. Some morbidities got worse during the pandemic among the elderly, such as Insomnia, Headaches, Depression, Tinnitus, among others. Conclusion Even though our data suggest that the pandemic did not have a great impact on quality of life, sleep quality and psychosocial aspects in the elderly, they were still affected by the worsening of their health conditions, including sleep and morbidities. Some behaviors may act as protective factors in this population, such as walking and keeping contact with others, as well as other aspects like financial stability, high level of education and family support, as they can help them to cope better with difficulties.